Penataan Dan Pengembangan Instalasi Listrik Fakultas Teknik UNSRAT 2017 - Andersen D. Prok; Hans Tumaliang; Marthinus Pakiding (Universitas Sam Ratulangi, 2018)
Abstractâ€” Electrical installation is one part of the power system, its application to buildings and electrical equipment. Can help distribute electrical energy to be used by consumers. To install of installations suitable for general use of electrical installation (PUIL), Indonesian National Standart (SNI), and aesthetic neatness of installation. Problems in electrical installation are still widely found in the field, in the faculty of UNSRAT techniques found probles in the installation of electrical installation, such as the neatness of the electrical installation path and the setting in the faculty of engineering building. This problems can not be shared, so the power obtained can not be utilized as it should be. Recognized with the problems of electric power installation in the faculty of engineering I took the title oft thesis â€œArrangement And Development Of Electricity Faculty Of Engineering UNSRAT 2017â€. From my research on electrical installation in the main buildings of faculty of UNSRAT technique, found the division in the main building faculty of UNSRAT engineering not per floor erratic. Observation made to know the division path, Main Panel Distribution (MDP) and Sub Panel Distribution (SDP). Structuring needs to be done for the appropriate division, according to the standarts and potential ofÂ solar cell development as a backup source in the engineering faculty can be considered for the foreseeable future.Â Â Keywords : Development, Electric Power Installation, Faculty Of Engineering UNSRAT, Structuring.Abstrakâ€” Instalasi listrik merupakan salah satu bagian dari sistem tenaga listrik, penerapannya terhadap bangunan dan peralatan tenaga listrik. Instalasi listrik membantu menyalurkan energi listrik agar dapat digunakan oleh konsumen. Pemasangan instalasi listrik yang sesuai standar harus menggunakan persyaratan umum instalasi listrik (PUIL), Standart Nasional Indonesia (SNI) serta estetika kerapihan pemasangan. Masalah dalam instalasi tenaga listrik masih banyak ditemukan dilapangan, di fakultas teknik unsrat ditemukan masalah dalam pemasangan instalasi listrik yang dilakukan, antara lain masalah kerapihan jalur instalasi listrik, dan pengaturan pembagian beban di gedung fakultas teknik, masalah ini mengakitbatkan pembagian tiap fasa tidak seimbang sehingga daya yang didapat tidak dapat di manfaatkan sebagai mana mestinya. Berdasarkan dengan masalah instalasi tenaga listrik di fakultas teknik saya mengambil judul skripsi â€œ Penataan dan Pengembangan Instalasi Listrik Fakultas Teknik Unsrat 2017â€. Dari penelitian yang saya lakukan terhadap masalah instalasi listrik di bangunan utama fakultas teknik unsrat, di temukan pembagian beban di gedung utama fakultas teknik unsrat tidak per lantai melainkan tidak menentu, Observasi yang dilakukan bertujuan untuk mengetahui jalur pembagian beban, besaran arus pada Main Distribution Panel (MDP) sertaÂ Sub Distribution Panel (SDP). Penataan perlu dilakukan untuk pembagian beban yang seimbang dan sesuai standar dan potensi pengembangan solar cell sebagai sumber daya cadangan di fakultas teknik dapat di pertimbangkan untuk kedepan.Kata kunciâ€” Fakultas Teknik UNSRAT, Instalasi tenaga listrik, Penataan, Pengembangan.